2017
DOI: 10.1007/s13593-017-0440-z
|View full text |Cite
|
Sign up to set email alerts
|

Azolla planting reduces methane emission and nitrogen fertilizer application in double rice cropping system in southern China

Abstract: Rice paddies are a major source of methane. How to reduce the methane emission in the paddy field without decreasing the yield has become a major concern of scientists, environmental groups, and agricultural policymakers worldwide. Azolla, used as a dual crop in rice cultivation, has multiple agronomic benefits. However, the effects of the dual cropping of Azolla on methane emissions of double rice cropping paddies have not yet been reported. Here, we conducted a 3-year field experiment to evaluate the impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…In this study, the positive effect of milk vetch on the subsequent rice crops is in agreement with results from Yu et al [23] and Zhu et al [17], which showed a 5-10% yield increase by including legumes such as bean or vetch in a rice-winter crop system. Similar positive effects on rice yield have been observed in multiple cropping systems such as rice-Azolla [24] and rice-fish [25]. In our study, milk vetch and subsequent early and late rice crops constituted a temporal multicropping system that resulted in enhanced rice crop yields.…”
Section: Effect Of Vetch Winter Cropping On Rice Grain Yieldsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, the positive effect of milk vetch on the subsequent rice crops is in agreement with results from Yu et al [23] and Zhu et al [17], which showed a 5-10% yield increase by including legumes such as bean or vetch in a rice-winter crop system. Similar positive effects on rice yield have been observed in multiple cropping systems such as rice-Azolla [24] and rice-fish [25]. In our study, milk vetch and subsequent early and late rice crops constituted a temporal multicropping system that resulted in enhanced rice crop yields.…”
Section: Effect Of Vetch Winter Cropping On Rice Grain Yieldsupporting
confidence: 84%
“…Others observed enhanced crop yield and N uptake with residue incorporation of a suitable C/N ratio and when applied at the right time or in a right way [12,28,29]. In this study, the low C/N ratio of the vetch biomass residue (20)(21)(22)(23)(24)(25) and 10 days between vetch incorporation and rice transplanting allowed enough time for N release coinciding with early rice growth resulting in increased grain yield and N uptake. The increase in late rice grain yields and N uptake in vetch covering treatments could be explained by a higher N return from early rice straw biomass incorporation before late rice transplanting.…”
Section: Effect Of Vetch On Rice N Uptake and N Use Efficiencymentioning
confidence: 66%
“…Additionally, Azolla has recently gained considerable importance for its multifaceted uses (Yadav et al 2014;Kollah, Patra, and Mohanty 2016;Shukla et al 2018;Chakraborty et al 2019). Use of Azolla as green manure can either be through its incorporation into paddy soil at the beginning of land preparation before rice transplanting or grown as a dual crop along with rice plants (Xu et al 2017). Dual cropping of Azolla with rice was reported to either increase (Chen et al 1997;Ying et al 2000) or decrease (Bharati et al 2000;Kimani et al 2018) CH 4 emission fluxes from flooded rice paddies with varying observations of N 2 O emissions reported as well (Chen et al 1995;Zou et al 2005;Kimani et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their high growth and N 2 fixation rates, Azolla ferns have been used as a bio‐fertilizer in rice paddies in south‐east Asia for several centuries . Using Azolla as bio‐fertilizer increases the sustainability of rice cultivation by reducing fertilizer requirement as well as reducing nitrogen and greenhouse gas (GHG) emissions from rice paddies . However, a direct use of Azolla biomass for feed production may provide more environmental benefits as well as economic value to farmers, but is not yet common on a large scale.…”
Section: Introductionmentioning
confidence: 99%